Alteration in cation specificity of the melibiose transport carrier of Escherichia coli due to replacement of proline 122 with serine. - Yazyu, H (1985)
The structural genes (melB) for the melibiose carrier of five mutants of Escherichia coli showing altered cation specificity for melibiose transport were cloned. The mutations were mapped in a 248-base-pair DNA fragment by a recombinational assay by using the mutants transformed with hybrid plasmids carrying various portions of the wild-type melB gene. The nucleotide sequences of the corresponding DNA fragments derived from mutated melB genes were determined, and the amino acid sequences of the carrier were deduced. Proline 122 was replaced with serine in the melibiose carrier of all five mutants (which were isolated independently). We conclude that this amino acid replacement caused the alteration in cation specificity (loss of coupling to H+) of the melibiose carrier.